Dutch soccer secrets : playing and coaching philosophy--coaching, tactics, technique - Hyballa, Peter , 1975-; Poel, Hans-Dieter te (Auckland, New Zealand : Meyer & Meyer Sport, 2012)
Learn how a nation of about 16 million inhabitants can regularly produce world-class players or coaches like Johan Cruyff, Arjen Robben or Dick Advocaat and Louis van Gaal
1. Following the "treasure map" of the 2010 world cup runners-up -- 2. State of the art -- 3. Talking about talent -- 4. The KNVB philosophy -- 5. The Dutch youth coach in clubs and associations -- 6. Playing, coaching and training philosophies in the Netherlands -- 7. Dutch techniques coaching in theory and practice -- 8. Dutch tactics coaching in theory and practice -- 9. Dutch conditioning training in theory and practice -- 10. Talent development at Ajax Amsterdam in theory and practice -- 11. Conclusion and outlook -- 12. Appendix
Includes bibliographical references (p. 222-231)
Keywords: Soccer -- Coaching; Soccer -- Training; Soccer -- Netherlands